Menumbuhkan Karakter: Merangkul Kearifan Lokal melalui Seni Teater Mamanda untuk Pembelajaran Kolaboratif: Fostering Character: Embracing Local Wisdom through Mamanda Theater Arts for Collaborative Learning - Kaspul Kaspul; Dasim Budimansyah; Chairil Faif Pasani; Momod Abdul Somad; Garuzooka John Francis (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2023)
This research explores the integration of character education, specifically focusing on drawing inspiration from the abundant cultural wisdom embedded in Mamanda theater—an invaluable cultural asset in South Kalimantan. The central aim of the study is to evaluate the effectiveness of utilizing Mamanda’s theater arts as a catalyst for collaborative character-building within the realm of education. The collaborative characters, symbolic of the harmonious dynamics inherent in the learning process, undergo evaluation through the implementation of a Likert scale. The research encompasses a cohort of 83 students, all actively engaged as respondents. The outcomes highlight the notably high effectiveness of incorporating Mamanda’s theater arts to facilitate the collaborative character-building endeavor. Beyond its immediate findings, this research contributes substantively to the ongoing academic dialogue surrounding character education. Moreover, it serves as a valuable resource for educators and lecturers, offering insights into the practical application of local wisdom, specifically through Mamanda theater, to instill character traits firmly rooted in cultural richness and educational excellence.